Arabic-Malay cognates as a computer assisted language learning - Shehab, Roaya; Zeki, Akram M. (IEEE, 2014)
This paper aims to build an Arabic WEB-based learning system for Malaysian learners focusing on cognate words in the Arabic language and Malay language. This paper focuses only on the highlighted cognates in the lessons interface in the WEB-based system. The paper starts by the importance of Computer-Assisted Language Learning (CALL), benefits of using cognates in leaning a foreign language, and the bower of highlighting vocabulary strategy in language learning. Finally, the paper concluded by the technical details of building the present WEB-based system.